Antibacterial and anti-inflammatory activity of bistort (Bistorta officinalis) aqueous extract and its major components. Justification of the usage of the medicinal plant material as a traditional topical agent. (5th October 2020) - Pawłowska, Karolina A.; Hałasa, Rafał; Dudek, Marta K.; Majdan, Magdalena; Jankowska, Katarzyna; Granica, Sebastian
Abstract: Ethnopharmacological relevance: Bistort rhizome ( Bistorta officinalis ) is a traditionally used plant material popular in Europe and Asia in the treatment of diarrhea and as a topical agent for skin conditions. It contains tannins mostly condensed flavan-3-ol derivatives. However, the in-depth phytochemical investigation of infusions from this plant materials is still lacking. Additionally, the scientific reports supporting the traditional topical application of bistort rhizome are scarce. Aim of the study: The major objective of the present study was to comprehensively investigate the chemical composition of infusion from subterranean parts of common bistort both using hyphenated chromatographic technique and isolation approach. Additionally, the influence of water extract on pro-inflammatory functions of human neutrophils was performed. As bacterial infections play a crucial role in the generation of skin inflammations the antimicrobial activity of the infusion and its major components was established. Material and methods: The chemical composition of the infusion was established using UHPLC-DAD-MS 3 method. Major compounds which could not be identified using chromatographic analysis were isolated by column chromatography and preparative HPLC. Obtained pure phytochemicals were identified by NMR analysis. The influence of the extract and compounds on the cell viability and apoptosis was evaluated by flow cytometry. The release of pro-inflammatory cytokines after LPS stimulation was established by ELISA. Finally, the antimicrobial assays were performed by establishing MIC and MBC values using several bacterial strains. Results: The UHPLC analysis revealed the infusion contained mainly, galloyl glucose derivatives, procyanidins and chlorogenic acid. Several compounds were isolated and identified for the first time from the investigated plant material. It was shown that the infusion and its constituents influenced the release of proinflammatory cytokines such as IL-1β, TNF-α and IL-8 and also affected the viability and apoptosis of healthy cells. Both extract and isolated natural products displayed antimicrobial activity against skin pathogens. Conclusions: The results obtained in the present study support that the infusions from common bistort influence key biological processes are crucial for skin conditions with the inflammatory background. The study justifies the traditional topical application of common bistort. Graphical abstract: Image 1 Highlights: Phytochemical composition of bistort rhizome was investigated. Flavon-3-ols and galloylglucose derivatives were isolated and identified. Anti-inflammatory activity of infusion and its constituents was checked. Justification for the traditional topical used was proposed. Antimicrobial activity against skin pathogens was evaluate.